The Oscillograms and the physiology of audition - Krishnamurthy KH (Journal of All India Institute of Speech and Hearing, 1972)
As the functioning of the cochlea is understood at present, the basilar membraneon the impact of sound waves registers distinctly recognisable movements. Thelatters' final mechanical effect however is the shearing action of the hairs of cortagainst the superjascent tectorial membrane (Davis, 1958; Zalin, 1961). Subsequentto this, cytochemical (Vinnikov and Titova, 1963 and 1964) and electrical (Wever,1966) changes take over. The mechanical reactions of the basilar membrane thusform a crucial step in audition. It is also recognised that among the variouscochlear structures it is this membrane that possesses the necessary extent, physicalproperty and histology (Engstrora, 1955) to effectively intervene within the cochlearfluids the passage of sound viz. the micropressure changes caused by it in the mediumand be responsible for handing it over further to the hair cells (Wever and Lawrence,1954). However, the observable mechanical as well as electrical responses of themembrane to the stimulus is known since long (Lawrence, 1966) to be considerablybroad while the actual auditory response is quite sharp. For instance, a greatdiscrepancy is noticeable in the resolution of pitch. Our descrimination of pitchesis fixer than what is indicated by the known responses of the membrane. For example,a trained ear can discern a change of even 2-3 frequency range in an incoming soundwhile the membrane's known responses are never so fine.